Metals composition in low cost apartment in Kuala Lumpur / Zitty Sarah Ismail … [et al.] - Ismail, Zitty Sarah; Wan Arba’in, Nur Farhana; Nik Ariffin, Nik Azlin; Muhammad, Mazhani; Muhamad Darus, Fairus; Mohd Firdaus Hum, Nurul Nadiah (Universiti Teknologi MARA, 2019)
House dust was found to be a great indicator of metal pollutants for indoor air quality. This study aims to assess the level of metals in house dusts and identify the relationship between the composition of metals concentration in low cost apartment, Kuala Lumpur. Eight houses were selected randomly from four levels of low cost apartment buildings. The samples were collected using a brush and plastic pan and then the samples were digested. The compositions of metals were determined using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) and statistical analysis was used to analyze the data by using Statistical Packages for the Social Sciences (SPSS). The results show that the highest concentration of metals obtained was Fe with the mean value of 1483.64 mg/kg followed by Zn with the mean value of 1197.07 mg/kg, while Cd recorded as the lowest mean value of 0.131 mg/kg. The trend distribution of metals in the investigated areas followed the order Fe > Zn > Cu > Pb > Cd. Statistical analysis indicates significant correlation between all the possible pairs of metals.